2015
DOI: 10.1534/genetics.115.181172
|View full text |Cite
|
Sign up to set email alerts
|

A New Player in the Spermiogenesis Pathway of Caenorhabditis elegans

Abstract: Precise timing of sperm activation ensures the greatest likelihood of fertilization. Precision in Caenorhabditis elegans sperm activation is ensured by external signaling, which induces the spherical spermatid to reorganize and extend a pseudopod for motility. Spermatid activation, also called spermiogenesis, is prevented from occurring prematurely by the activity of SPE-6 and perhaps other proteins, termed "the brake model." Here, we identify the spe-47 gene from the hc198 mutation that causes premature sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…When we first discovered that spe-47 harbored the hc198 mutation that suppressed spe-27(it132ts) sterility by inducing premature spermatid activation [ 18 ], we became aware that there was a closely-related paralog present in the genome: Y48B6A.5 ( Fig 1A and 1B ). The SPE-47 and Y48B6A.5 proteins exhibit a high degree of sequence conservation, with both having an N-terminus of unknown function and a C-terminal MSP domain that lacks the final β strand ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…When we first discovered that spe-47 harbored the hc198 mutation that suppressed spe-27(it132ts) sterility by inducing premature spermatid activation [ 18 ], we became aware that there was a closely-related paralog present in the genome: Y48B6A.5 ( Fig 1A and 1B ). The SPE-47 and Y48B6A.5 proteins exhibit a high degree of sequence conservation, with both having an N-terminus of unknown function and a C-terminal MSP domain that lacks the final β strand ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…When we first discovered that spe-47 harbored the hc198 mutation that suppressed spe-27(it132ts) sterility by inducing premature spermatid activation [18], we became aware that there was a closely-related paralog present in the genome: Y48B6A.5 (Fig 1 A&B). The SPE-47 and SPE-50 proteins exhibit a high degree of sequence conservation, with both having an N-terminus of unknown function and a C-terminal MSP domain that lacks the final ß strand (Fig 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…The spe-27 mutation causes hermaphrodite sterility because the self-spermatids are unresponsive to the signal to activate [32]. The spe-47(hc198) mutation recovered from the screen causes some spermatids to activate precociously without the need for an activation signal, overcoming the sterility of spe-27(it132ts) (Fig 4) [18]. If SPE-50 is functionally redundant to SPE-47, then a mutation similar to hc198 in spe-50 should also result in precocious spermatid activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways functioned redundantly in ancestral males [ 29 ]. Characterizations of an identified spe-47 ( hc198 ) allele using the CRISPR system showed that the hc198 mutation is able to bypass the SPE-8 signaling pathway to cause premature activation of a small fraction of sperm [ 63 ]. In addition, the authors have found that the nucleosome remodeling factor (NURF) complex has acquired a unique role in the sperm/oocyte decision of C. briggsae [ 62 ].…”
Section: Important Results Achieved Using Genome Editing Techniquementioning
confidence: 99%